On the original formulation and on the resonance over time of Grassmann’s Law: remarks on a still open issue - Pozza, Marianna (Lingua Posnaniensis, 2019)
The present article aims to reconsider in detail the original formulation of Grassmann’s law (GL), proposed by Grassmann (1863), since the main handbooks of Indo-European linguistics often repeat an extremely concise and sometimes incomplete formulation of the phenomenon without going into the details of Grassmann’s original reasoning, from which the definition of the phonetic “law” took its shape. In fact, we intend to highlight, on the one hand, the route whereby the scholar arrived at the decisive formulation of the principle which took its name from him, on the other the research ideas already present in the article of 1863 and only partially taken into account by subsequent studies. In addition to offering an overview, as complete as possible, of the resonance and influence of GL among linguists (both within a general and a historical linguistic perspective), over the years, the intent is to show the fruitfulness of ideas that still today could be used for new studies on the topic and to offer a possible, new interpretation of this phonetic change.